Front Cover: Influence of Chloride and Nitrate Anions on Copper Electrodeposition onto Au(111) from Deep Eutectic Solvents (ChemElectroChem 19/2022). Issue 19 (12th September 2022) - Geng, Tanja; Schick, Benjamin W.; Uhl, Matthias; Kuehne, Alexander J. C.; Kibler, Ludwig A.; Ceblin, Maximilian U.; Jacob, Timo
Abstract : The Front Cover illustrates copper electrodeposition on a gold‐coated quartz crystal from a choline chloride/ethylene glycol deep eutectic solvent (DES) in the molar ratio 1:2 with copper(II) chloride. Investigations conducted in an electrochemical quartz crystal microbalance (EQCM) revealed that the deposition occurs by a one‐electron reduction from Cu + . More information can be found in the Research Article by T. Geng et al .